Animal metaphors and the people of Israel in the Book of Jeremiah - Foreman, Benjamin A. (Forschungen zur Religion und Literatur des Alten und Neuen Testaments, 2011)
This book examines the language and imagery of the animal metaphors for the people of Israel in the book of Jeremiah and argues that these metaphors are essential to the theology of the book. Though interest in the use of metaphor in the Hebrew Bible has gained momentum in recent years, there is, to date, no investigation which concentrates exclusively on the animal metaphors in the book of Jeremiah. In this volume Foreman brings to light this neglected area of study by examining the language and imagery of the animal metaphors for the people of Israel. Since different interpretations have been given to many of the metaphors in question, the author resolves some of the questions regarding the meaning of these images in his in-depth study.